2010
DOI: 10.1111/j.1365-2621.2010.02369.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of volatile compounds in papaya wine fermented with three Williopsis saturnus yeasts

Abstract: The changes in volatile compounds during papaya juice fermentation with three Williopsis saturnus yeasts were investigated in this study. Time-course papaya juice fermentations were carried out using three Williopsis saturnus yeasts: W. saturnus var. mrakii NCYC2251, W. saturnus var. saturnus NCYC22 and W. saturnus var. sargentensis NCYC2727. Changes in yeast cell population, Brix and pH were similar among the three yeasts, which preferentially utilised glucose over fructose while partially degrading l-malic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 32 publications
6
75
0
Order By: Relevance
“…Other researchers have also observed the comparatively slower growth rates of Williopsis yeasts (17,18). It has been shown that the intensity of fermentation (defi ned as the average number of days elapsing between inoculation of the glucose fermentation tube and the reduction of gas volume in the insert) with W. saturnus var.…”
Section: Yeast Growth Total Soluble Solids and Ph Changesmentioning
confidence: 99%
“…Other researchers have also observed the comparatively slower growth rates of Williopsis yeasts (17,18). It has been shown that the intensity of fermentation (defi ned as the average number of days elapsing between inoculation of the glucose fermentation tube and the reduction of gas volume in the insert) with W. saturnus var.…”
Section: Yeast Growth Total Soluble Solids and Ph Changesmentioning
confidence: 99%
“…mrakii NCYC2251 was obtained from the National Collection of Yeast Cultures (Norwich, UK) and propagated following the procedure described by Lee et al (2010). L-Leucine, L-isoleucine, L-valine, L-phenylalanine, fructose, glucose, acetic acid, citric acid, DL-malic acid and DL-tartaric acid were purchased from Sigma-Aldrich (Oakville, ON, Canada).…”
Section: Yeast Strain and Materialsmentioning
confidence: 99%
“…The preparation and fermentation of the papaya juice were based on the procedure described by Lee et al (2010). Papayas of the Sekaki cultivar were washed, juiced and centrifuged (32,140 x g for 15 min at 4°C).…”
Section: Fermentation Conditionsmentioning
confidence: 99%
“…W. mrakii, formerly known as Hansenula mrakii, is an efficient producer of acetate esters (Li et al, 2012). The yeast has been inoculated to improve the fruity character of Japanese sake (Inoue et al, 1997), grape wine (Erten & TAnguLer, 2010) and papaya wine (Lee et al, 2010). This research is to assess the influence of S. cerevisiae and W. mrakii as both mono-and mixedcultures on mango wine characteristics.…”
mentioning
confidence: 99%